1988
DOI: 10.1111/j.1365-2788.1988.tb01387.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaving home: the experience of people with a mental handicap

Abstract: ABSTRACT. Open‐ended interviews were conducted with 12 people with a mental handicap who had left parental homes in order to live as tenants in community residential hostels. Parents and hostel staff were also interviewed. The nature of life in the family home, and the tenant's role in the move, reasons for leaving home and expectations for the future were explored. It was found that social life, autonomy and opportunities to develop self‐help skills had been limited at home. The tenants who had the widest so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The present authors' own research (Cattermole et al, 1988 has shown that people with mild learning difficulties are acutely aware of not having adequate interactions with other people and of being treated as second class citizens, or 'like a school bairn' (Jahoda et al, 1989); of getting sympathy from others because of being handicapped rather than treated as a person in his or her own right (Jahoda et al, 1987). Moreover, other research findings have shown that the opportunities for social interactions of people with learning difficulties and their degree of satisfaction with their lives is central to their sense of personal identity and feeling that they belong somewhere .…”
Section: Introductionmentioning
confidence: 88%
“…The present authors' own research (Cattermole et al, 1988 has shown that people with mild learning difficulties are acutely aware of not having adequate interactions with other people and of being treated as second class citizens, or 'like a school bairn' (Jahoda et al, 1989); of getting sympathy from others because of being handicapped rather than treated as a person in his or her own right (Jahoda et al, 1987). Moreover, other research findings have shown that the opportunities for social interactions of people with learning difficulties and their degree of satisfaction with their lives is central to their sense of personal identity and feeling that they belong somewhere .…”
Section: Introductionmentioning
confidence: 88%
“…Negative perceptions and stigma associated with receiving assistance, particularly assistance that requires a change in residence, may also influence decisions. Despite fears expressed by seniors regarding a loss of autonomy and restrictions associated with assisted living facilities (Jungers 2010), individuals with intellectual or developmental disabilities report an increase in independence as a primary reason for moving from their caregivers' home to a care facility (Cattermole et al 1988). Finally, a desire to avoid placing burden on family members may increase the likelihood of moving to a care facility (Jungers 2010).…”
Section: Factors Contributing To Decisions Regarding Living Arrangementsmentioning
confidence: 99%
“…The latter lends support to the statement made by Landesman & Butterfield (1987) that, 'Given adequate support systems, most severely and profoundly retarded individuals, even some with severe behaviour or health problems, can progress in settings other than large, traditional institutions.' Investigations by Flynn & Saleen (1986) and by Cattermole et al (1988) looked at restrictions placed upon adults with mental retardation who were living with their families. A number of these individuals expressed frustration with the fact that they were not allowed to employ home skills which were learned at their day programmes.…”
Section: Introductionmentioning
confidence: 99%
“…However, it must be noted that several of these studies (Cattermole et al, 1988: Flynn & Saleen, 1986Jahoda et al, 1988;Raynes et al, 1987) were conducted in Great Britain and Scotland, where public policies and attitudes differ somewhat froni those in the United States. In addition, sample sizes were often small (n<50) Therefore, this author is unsure of the extent to which the results of these studies may be applied to the field of study of the capabilities and needs of the mentally retarded population in the United States.…”
Section: Introductionmentioning
confidence: 99%